Poklonenie v Tronnom zale (Otk. 4,5): poisk germenevtičeskogo protoobraza i bogoslovskogo značenija - Beljaev, Aleksandr (Bogoslovskie razmyšlenija, 2011)
Reading of the book of Revelation raises many hermeneutic, isagogic, exegetical, and theological questions. The author touches two main questions: (1) hermeneutic proto-image of worship in the Throne Hall in Rev. 4, 5 and the analysis of potential interpretations; (2) within the theological analysis we answer to the question what principles for the worship practice in today life we might take from the given biblical passage.